My visit to the aquarium - Aliki ([New York] : HarperCollins, 1993)
During his visit to an aquarium, a boy finds out about the characteristics and environments of many different marine and freshwater creatures.
Elem. School Library Collection
School Library Journal starred
Wilson's Children
3.9
K-3
K-3
Keywords: Aquariums, Public -- Juvenile literature; Aquatic biology -- Juvenile literature; Aquariums, Public; Aquatic biology; Freshwater animals; Marine animals; Aquariums; Freshwater animals; Freshwater biology; Marine animals; Marine biology